Reflexive ethnography as a tool in researching Hungarian Krishna devotees reflections on the margin of a long-term fieldwork among the Hungarian Community of Sri Chaitanya Saraswat Math - Bodosi-Kocsis, Nóra (Sacra, 2012)
The paper deals with some aspects of reflexive fieldwork by analysing the author's Couchsurfing experience in Brno during the workshop "Towards a Symmetrical Approach: The Study of Religions after Postmodern and Postcolonial Criticism". The experience is interpreted as a field situation and the author is regarded as an ethnographer. The author's modes and codes of behaviour are being scrutinized in a reflexive way. The situation and its reflexive analysis can throw light upon certain modes of fieldwork practices which stayed unnoticed during real field situations among a certain group of Hungarian Krishna devotees; the Hungarian Community of Sri Chaitnya Saraswat Math. Making these actions of the researcher conscious may help producing more honest and sensitive ethnographies and may offer a deeper insight into the complex nature of ethnographic fieldwork. In addition, the experience can be useful in my research among Krishna devotees.